Collaboration In Developing Islamic Micro Finance Institutions (IMFs) Based On Financial Technology - Elida Elfi Barus (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2021)
In the era of industry 4.0 and the current pandemic, existence of Islamic microfinance institutions, especially sharia cooperatives, have fallen with many obstacles. Therefore, various capital innovations with Company to Company (C2C) collaboration are needed. This collaboration needs to be supported by an accommodating system, so that its development can provide benefits to users, one of which is influenced by the use of Ammana.id's. this is an Islamic fintech which is also assisted by other actors such as regulators, conceptors, owners, mentors and the community (pentahelix) by analyzing the development strategy of Islamic cooperatives with fintech collaboration with the pentahelix approach by interpretative structural modeling (ISM). This paper found that the elements of actors that are Department of Cooperatives and Small-Medium Enterprises are the key elements so that it needs to focus on developing sharia regulations which are then assisted by academics as conceptors in the development of islamic micro finance institutions. Keyword : Collaboration, Sharia Financial Technology, pentahelix